Job insecurity during the COVID-19 pandemic and counterproductive work behavior: The sequential mediation effects of job stress and organizational identification and the buffering role of corporate social responsibility - Kim, Byung-Jik; Lee, Julak; Jung, Jeyong; Kim, Min-Jik (Frontiers in Public Health, 2023)
Swift social and economic environmental changes such as the COVID 19 pandemic has increased the degree of employees’ job insecurity. Although numerous previous studies have examined the influence of job insecurity on employee’s perceptions, attitudes, and behaviors, the job insecurity-negative behavior link and its underlying or intermediating mechanisms remain underexplored. Also, existing scholars paid less attention to the significance of organization's good and benevolent behaviors such as corporate social responsibility (CSR). To address these gaps, this study delved into both the mediator and the moderator in the association between job insecurity and employee’s negative behavior by establishing a moderated sequential mediation model. The current paper hypothesizes that the level of employee job stress and organizational identification may sequentially mediate the job insecurity-counterproductive work behavior, as a representative negative behavior. In addition, CSR activities would play a buffering role that moderates the influence of job insecurity on job stress. With three-wave time-lagged data that was collected from 348 employees in South Korean organizations, the current research demonstrated that not only job stress and organizational identification sequentially mediate the job insecurity-counterproductive work behavior, but also CSR activities function as a buffering factor that decreases the influence of job insecurity on job stress. The results of this research suggest that the level of job stress and organizational identification (as sequential mediators) as well as CSR activities (as a moderator) are underlying processes in the job insecurity-counterproductive work behavior link.